Evaluasi Pengamanan Barang Milik Daerah (Studi Kasus Pada Dinas Pendidikan, Pemuda dan Olahraga Pemerintah Daerah Kabupaten Pontianak) - , Uray Muhammad Nur ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was aimed to know and to evaluate the manners to manage assets, especially securing assets, in evaluating assets security the writer used a primary and secondary data source obtained from Assets Department (as an authority of Assets Administrator), Account Department of Income Office, Regional Financial and Asset Management (DPPKAD), and also in the research site namely The Office of Educational, Youth and Sports, especially in the department that was responsible in assets storage and assets arrangement. This was a case study research with a descriptive analytical technique in order to illustrate, summarize various conditions, various situations and also as a reality phenomenon that was a research object and attempted to draw a reality to the public as characteristics, character, attitude, model, sign and image in securing assets in Regional Government of Pontianak Regency. Therefore, an attributive and substantive evaluation and analysis could give a criteria comparison from securing assets according to standard rules and regulations with a securing applied in Pontianak Regency as a reality to observe. From the comparison between a standard criteria as well as its application was tested using a Criteria Reference Test (CRT). In obtaining a numerical from a CRT it used a specific criteria namely continuum (range) or by giving a specific number. The selection of this score was related to the judgment result and evaluation purpose due to the judgment purpose was to select based on a âsuitableâ and ânot suitableâ classifications. In this research, an aspect that was evaluated would be judged according to the facts found in the research site, and the judgment fitted and according to rules and regulations issued by the central government. One of regulations as a principle to evaluate securing assets was Permendagri Number 17 of 2007 on Assets Management. The result was to see how far the implementation of the governmental regulations on assets management applied in an effort to secure assets in The Regional Governmental operational so far. The research result obtained that assets were only important when there was an asset buying and an asset selling so that it could be understood if in the Regional Government only applied Permendagri Number 17 of 2007 in a writing-off cycle only, while other cycles had not been implemented.